2013
DOI: 10.1007/s00726-013-1553-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and membrane transporters

Abstract: In recent years, our understanding of the importance of membrane transporters (MTs) in the disposition of and response to drugs has increased significantly. MTs are proteins that regulate the transport of endogenous molecules and xenobiotics across the cell membrane. In mammals, two super-families have been identified: ATP-binding cassette (ABC) and solute carrier (SLC) transporters. There is evidence that MTs might mediate polyamines (PA) transport. PA are ubiquitous polycations which are found in all living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 51 publications
1
75
0
2
Order By: Relevance
“…The absorption of AA requires many transporter systems that differ with respect to their substrate specificity and driving force (Wang et al, 2009). It has been reported that some genes (such as ASCT2, EAAC1, B 0+ AT, y + LAT1, 4F2hc, and ATB 0 ) that are involved in the control of growth or AA metabolism are regulated by AA availability (Wu, 1998;Lallès et al, 2007;Zhang et al, 2012;Abdulhussein and Wallace, 2014). In our study, we found that, with an increase in the dietary CP level, the expression of AA transporter genes (ASCT2, EAAC1, B 0+ AT, 4F2hc, and ATB 0 ) tended to increase, while an opposite trend was seen related to the abundance of y + LAT1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of AA requires many transporter systems that differ with respect to their substrate specificity and driving force (Wang et al, 2009). It has been reported that some genes (such as ASCT2, EAAC1, B 0+ AT, y + LAT1, 4F2hc, and ATB 0 ) that are involved in the control of growth or AA metabolism are regulated by AA availability (Wu, 1998;Lallès et al, 2007;Zhang et al, 2012;Abdulhussein and Wallace, 2014). In our study, we found that, with an increase in the dietary CP level, the expression of AA transporter genes (ASCT2, EAAC1, B 0+ AT, 4F2hc, and ATB 0 ) tended to increase, while an opposite trend was seen related to the abundance of y + LAT1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PA transport systems have been a subject of interest. Although the major source of PAs is thought to be via de novo biosynthesis, PA uptake and transport are also considered to have signifi cant roles in PA homeostasis (Abdulhussein and Wallace 2014 ;Igarashi and Kashiwagi 2010 ). In plant cells, PAs are localized in cell walls, vacuoles, nuclei, mitochondria, and chloroplasts (Slocum and Flores 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, the internal concentration of polyamines is regulated metabolically and through membrane transport [1,23,29] . Several bacteria isolated from human milk have been identified as putrescine producers, which may be a species-level characteristic [30,31] .…”
Section: Milk Polyamines and Microbiotamentioning
confidence: 99%